(untitled) (Medical Forum Monthly, 2024)
Objective: To record the frequency of retinopathy in newly diagnosed diabetes mellitus type II patients. Study Design: Cross Sectional survey Place and Duration of Study: This study was conducted at the Department of Ophthalmology, Helper’s Eye Hospital, Quetta from 1st July 2015 to 31st December 2016. Materials and Methods: A total of 200 newly diagnosed Type II diabetes mellitus patients of both gender and age between 30-65 years were enrolled in the study. Fundoscopy was performed by single consultant ophthalmologist to avoid any biasness while diagnosing retinopathy. The frequency of retinopathy in cases with newly diagnosed diabetes mellitus type II was noted. Results: In our study, out of 200 cases, 80%(n=160) were between 30-50 years of age while 20%(n=40) were between 51-70 years of age, mean age was 47.13+6.10 years, 55% (n=110) were male and 45% (n=90) were females, 19.5%(n=39) had diabetic retinopathy in newly diagnosed cases of type II diabetics. Conclusion: Frequency of diabetic retinopathy shows a significant incidence in type 2 diabetes mellitus, these findings will be helpful for timely management of the morbidity for saving our patients from visual loss.